Brain meta-state transitions demarcate thoughts across task contexts exposing the mental noise of trait neuroticism - Julie Tseng (Nature Portfolio, 2020)
Explicit self-reflection is unreliable for measuring thoughts. Here, the authors use brain data to implicitly pinpoint transitions between thoughts and find thought turnover to be reliably predicted by narrative events during movie-viewing, as well as by greater trait neuroticism at rest.